2021
DOI: 10.1111/are.15124
|View full text |Cite
|
Sign up to set email alerts
|

Control ofVibrioparahaemolyticus(AHPND strain) and improvement of water quality using nanobubble technology

Abstract: Nanobubble technology is used in wastewater treatment, but its disinfectant properties in aquaculture have not been clearly demonstrated. This study investigated the ability of nanobubbles to reduce Vibrio parahaemolyticus (AHPND strain) and to improve water quality. Two laboratory experiments were conducted over a one‐week period, that is (a) assessing the effects of air and oxygen nanobubbles for 60 minutes per day and (b) comparing effects of ozone nanobubble treatments for 2, 4 and 6 minutes per day. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…Importantly, the possible negative influence achieved by other magnesium metabolites and/or possible pH alteration in the metallic magnesium-produced HRW could not be easily ruled out. A similar disadvantage was recently reported when magnesium hydride (MgH 2 ) was used as a preservative for prolonging the vase life of cut flowers [22].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Importantly, the possible negative influence achieved by other magnesium metabolites and/or possible pH alteration in the metallic magnesium-produced HRW could not be easily ruled out. A similar disadvantage was recently reported when magnesium hydride (MgH 2 ) was used as a preservative for prolonging the vase life of cut flowers [22].…”
Section: Discussionsupporting
confidence: 59%
“…Hydrogen-rich water (HRW) or saline is a typical form of molecular hydrogen used in plants and medicine, due to its feasibility and safety in laboratory [14]. While the low solubility and short residence time of H 2 limit its wide application in practice, especially in paddy field, previous results have revealed that nano-bubble technology could be applied in aquaculture [22] and environment [23], since this approach could increase the content of targeted gas in water, prolong the time of the gas remaining in liquid, and improve the utilization efficiency of targeted gas. A recent study further discovered that the hydrogen nanobubble water (HNW) could alleviate copper toxicity in Daphnia magna since it could increase the solubility and the residence time of H 2 in water, therefore efficiently enhancing antioxidant capacity [24].…”
Section: Introductionmentioning
confidence: 99%
“…While improvement of water quality and oxygen levels can reduce the concentration of AHPND-causing Vibrio ( 39 ), and farmers have used broad-spectrum antibiotics to inhibit gram-negative bacteria and parasites ( 40 ), these measures cannot prevent outbreaks of pathogenic bacteria. Furthermore, inappropriate use of broad-spectrum antibiotics may result in multidrug-resistant bacteria that exacerbate the risk of outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Joni et al [17] also reported that the application of MiBs in an aquaculture system increased the DO from 4.5 mg L −1 to 7.9 mg L −1 . In addition to their use in aquaculture facilities, MiBs have been used to improve the water quality of wastewater contaminated with various hazardous materials, such as azo dye [18], methylene blue [19], phenol [6,20], palm oil [8], diesel oil [21], trichloroethylene [22], surfactants [3], pesticides [23], and pathogenic bacteria [24]. MiBs have also been used to remove microalgal cells [25] and planktonic crustaceans [26].…”
Section: Introductionmentioning
confidence: 99%